Z-copy Voltage Controlled Current Follower Differential Input Transconductance Amplifier in Controllable Biquadratic Band-Pass Filter - Sotner, Roman; Jerabek, Jan; Dostal, Tomas; Vrba, Kamil (Elektronika ir Elektrotechnika, 2016)
This paper presents the results of study on utilization of Z-copy Voltage Controlled Current Follower Differential Input Transconductance Amplifier (ZC-VCCFDITA) active element in a single purpose filtering structure. This active element has three voltage-controlled parameters (intrinsic resistance of current input, voltage gain and transconductance of output section) and is very useful for design of oscillators, signal generators and frequency filters with just one active element. In this paper, the important parameters of possible behavioural model of ZC-VCCFDITA are shown and a particular solution of the controllable band-pass filter is presented. Theoretical, calculated, simulated and moreover also measured results are mutually compared. DOI: http://dx.doi.org/10.5755/j01.eie.22.4.15911